PENGARUH SUPLEMENTASI MINYAK SAFFLOWER (CARTHAMUS TINCTORIUS L) DAN INOSITOL TERHADAP BOBOT TELUR DAN KETEBALAN KERABANG TELUR AYAM SENTUL - Hasanah, Lailattun; Ismoyowati, Ismoyowati; Tugiyanti, Elly (ANGON: Journal of Animal Science and Technology, 2021)
Backgrund. The purpose of this study was to examine and to find the best percentage of safflower oil and inositol supplementation on egg weight and shell thickness of sentul chicken. Materials and Methods. The material used in this study was 17 weeks and 243 eggs. The method used is experimental with a completely randomized design (CRD) with the treatments included R0: Control, R1: 0.5% safflower oil, R2: 1.0% safflower oil, R3: 0.5% Inositol, R4 : Inositol 0.1%, R5: Safflower Oil 0.5% and Inositol 0.5%, R6: Safflower Oil 0.5% and Inositol 1.0%, R7: Safflower Oil 1 , 0% and Inositol 0.5%, R8: Safflower Oil 1.0% and Inositol 1.0%. The data that have been obtained are analyzed using analysis of variance followed by honesty significant different further tests. Results. The results showed that supplementation of safflower oil and inositol had no significant effect (P> 0.05) on egg weight and eggshell thickness. The average egg weight was 36.00 ± 2.75 g; 37.20 ± 0.23 g; 39.18 ± 3.36 g;38.52 ± 4.20 g;37.68 ± 0.09 g;36.67 ± 1.04 g; 35.54 ± 2.14 g; 37.66 ± 1.01 g; 37.33 ± 1.85 g and the average thickness of shell is 0.41 ± 0.009 mm; 0.40 ± 0.022 mm; 0.43 ± 0.013 mm; 0.43 ± 0.026 mm;0.41 ± 0.004 mm; 0.42 ± 0.021 mm; 0.40 ± 0.031 mm; 0.38 ± 0.015 mm; 0.41 ± 0.029 mm. Conclusion. It can be concluded that supplementation of safflower oil and inositol produce relatively equal egg weights and shell thickness.